Social Presence And Video Conference In Professional Education - Bertagnolli, Gissele B. Leal; Quaresma da Silva, Denise Regina (International Journal for Innovation Education and Research, 2019)
This qualitative and exploratory study aims to analyze the use of technology applied to vocational education from the theoretical review of the concept of social presence and the use of videoconference as an effective technological instrument in the consecration of social inclusion and interaction. In the face of worldwide globalization, need for qualification and professionalization of individuals is incorporated, with the modality of Distance Education being seen as an emerging strategy in the search for alternatives for this purpose. Within the results, two categories were listed and analyzed: professional education through videoconferences and social presence in the technological context. It is concluded that vocational education through videoconferences has been employed in order to face the demands of the labor market, qualifying workers and collaborating with the inclusion of those outside the productive process of the social system, with education being one of the main means for the realization of what we refer to as social inclusion. It is believed that cultural changes would be able to achieve a teaching method that should be seen as a social necessity, irrigated by the interaction of the subject through technologies and social presence, penetrating the entire social structure.